1989
DOI: 10.1111/j.1365-2125.1989.tb03523.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the immediate and long‐term effects of captopril and isosorbide dinitrate as adjunctive treatment in mild heart failure.

Abstract: 1. The efficacy of captopril and isosorbide dinitrate (ISDN) as adjunctive therapy to digoxin and diuretics in mild heart failure was compared in a double‐blind study. 2. Twenty‐one patients were randomly allocated to captopril (twice or three times daily) or ISDN. Eighteen patients completed a protocol of placebo run‐in, dose titration and maintenance treatment for 3 months. 3. Symptom‐limited exercise tolerance, ejection fraction and radionuclide indices of diastolic function estimated by gated blood pool sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…"-" Captopril was given in a low dosage and only twice a day. Wilkes et al 24 showed that twice daily dosage of captopril is effective in patients with mild heart failure. This dose regimen does not provide roundthe-clock inhibition of the plasma reninangiotensin system.…”
Section: Discussionmentioning
confidence: 99%
“…"-" Captopril was given in a low dosage and only twice a day. Wilkes et al 24 showed that twice daily dosage of captopril is effective in patients with mild heart failure. This dose regimen does not provide roundthe-clock inhibition of the plasma reninangiotensin system.…”
Section: Discussionmentioning
confidence: 99%
“…Nitrate therapy has been examined in a similarly small patient cohort of 21 patients with heart failure and an EF greater than 40% [33]. These patients were randomly assigned to receive isosorbide dinitrate (n = 21) or placebo (n = 18) for 3 months.…”
Section: Introductionmentioning
confidence: 99%